Thorkild Dahls daggerter - Larsen, Lars Krants (Kuml, 2007)
Daggers from the Middle Ages On entering the front door to Moesgård’s 226 year old main building, some of the first objects to meet one’s eyes are two magnificent white mineral cabinets in Louis XVI style. These beautiful cabinets are among the oldest pieces of furniture at Moesgård. They originate from Christian Frederik Güldencrone’s time (1741-88) and contain now – as then – a mineralogical collection (fig. 1). In a lower drawer of one of the cabinets there are, however, two daggers that have nothing to do with this collection and which must have been added on a later occasion. The types of dagger which will be dealt with here are the kidney dagger and the so-called lansquenet dagger mentioned below. They have their origins in the Middle Ages and they are, due to their form, closely linked with the military equipment, especially the plate armour, increasingly in vogue during the 14th century. When the dagger became part of the knight’s armament it was in order for it to be used in hand-to-hand fighting. With its strong and rigid blade, the dagger could be pushed between the plates of a fallen knight’s armour, enabling the final and decisive coup de grâce to be given (fig. 2). The military zenith of the dagger was in the 14th-15th centuries. Daggers are often difficult to date. Many have been recovered from bogs and lakes and a great number do not have any associated information about their origin. As a consequence, the typological chronologies that have been produced are rather coarse-grained and are mainly based on pictorial sources and collections of historical weapons (fig. 3). One of the daggers is a double-edged kidney dagger, listed as No. 6 in the catalogue (fig. 4). The length of the dagger is 30 cm, of which 10.5 cm comprises the grip and 19.5 cm the blade. The grip is made of root wood, while the blade is of iron. The blade is rather slender, no more than 1.4 cm at its widest. No smith’s stamp or mark is visible. Below each kidney, traces of a now missing quillon-plate can be seen; this was often curved or wing-shaped. The guard had been attached to the kidneys by way of two sprigs. At the end of the hilt, a knob or boss has been carved out of the root wood and between the boss and hilt runs a bead which is now somewhat effaced. X-radiography reveals that the dagger has no real tang. The kidney dagger was quite often depicted in medieval times. An illustration in the so-called “Kristina Psalter”, thought to have been produced in Paris about AD 1230, is usually recognised as the oldest image of a kidney dagger. The dagger referred to is, however, very difficult to recognise as a kidney dagger; it is more probably of the high medieval dagger type – the cultellus. More certainty surrounds another rendition of a kidney dagger – that seen on Duke Christopher’s sepulchral monument from the AD 1360s in Roskilde Cathedral. This is usually regarded as Denmark’s oldest, securely dated kidney dagger (fig. 5). Another example to which attention is always drawn is the dagger shown at Valdemar Atterdag’s side on a fresco from about AD 1375 in St Peder’s Church in Næstved (fig. 6). The Moesgård dagger is dated to the period from the last quarter of the 14th century to the end of the 15th century. The kidney dagger has an interesting cultural history, not exclusively involving the art of war. Daggers become part of the rather dandified men’s fashion of the 15th century where the dagger was worn at front, hung on a belt. As can be imagined, it is no longer the kidneys one thinks about when seeing the dagger! This was also clear at the time; in England the dagger was referred to as the ballock dagger and in France dague á couilettes (fig. 7). The other dagger from the Moesgård cabinet is a so-called lansquenet dagger, listed as No. 17 in the catalogue. Like the kidney dagger this is a double-edged weapon (fig. 8). It is reminiscent of a small sword with short, straight or slightly bent quillons. The length of the dagger is 36.5 cm, of which the grip comprises 11 cm and the blade 25.5 cm. At the end of the tang a cone-shaped pommel with spiral grooves can be seen; this feature is repeated in the quillon terminals. Between quillon and tang, and between pommel and tang, narrow bronze casings can be seen – the last remnants of the lost grip. The double-edged blade, which has a maximum width of 2.1 cm, has a very strongly accentuated back; the cross-section between back and blade is almost concave. During the 15th century the composition and structure of armies gradually changed so that, with time, the heavily armoured cavalry were replaced by lighter infantry, armed with spears, swords and halberds. The infantry became more professional and in Germany, in the 15th century, were referred to as mercenaries; it is probably here that this type of dagger originated. There are several types of the so-called lansquenet dagger; variation is seen primarily in the shape and construction of the guard, but also the shape of the grip. Information from better preserved examples of the type, to which the Moesgård dagger belongs, suggests that the missing grip was probably of wood and was baluster-shaped. The sheath for a this type of dagger was often rather special, being made of wood and having a circular or oval cross-section and often several rows of horizontal beading. Some examples are iron-plated and heavy, and could be used as clubs in self-defence. The Moesgård dagger is dated to the 16th century, probably towards the end of the century. One further dagger, or rather the grip from a dagger, will also be dealt with here. This artefact was not, however, found in Dahl’s mineral cabinets but during an excavation alongside Århus Å in 2002. The degraded grip is made from a bovine metatarsal, carved to resemble twisted rope. It is listed in the catalogue as No. 7 (fig. 9). The grip is 10.3 cm long. The bone has been split lengthways and only the hint of one kidney is preserved. The artefact is dated to the latter half of the 15th century. The actual prototype for this piece is to be found among the magnificent daggers with grips fashioned from twisted bars of precious metal. In the earlier literature this type is dated to the 14th century but the evidence now indicates that it belongs to the latter half of the 15th century. Is a catalogue of the kidney and so-called lansquenet daggers from the Middle Ages and the Renaissance, which are either kept at museums in the Århus area or were found within Moesgård Museum’s area of archaeological responsibility. The main part of the collection is kept at Den Gamle By in Aarhus, and some of these daggers were previously published by A. Bruhn in 1950. Eighteen kidney and mercenary daggers are catalogued; further to these are six daggers, which cannot be assigned more precisely to type. Seven daggers are of unknown origin. It should be noted that 10 out of the remaining 17 daggers were found either in a lake, watercourse or bog. This significantly high proportion is probably not just due chance but no real investigation has ever been carried out into this phenomenon. Only two of the daggers were found during actual archaeological excavations. Lars Krants Larsen Moesgård Museum